2022
DOI: 10.1093/plcell/koac219
|View full text |Cite
|
Sign up to set email alerts
|

The renaissance and enlightenment ofMarchantiaas a model system

Abstract: The liverwort Marchantia polymorpha has been utilized as a model for biological studies since the 18th century. In the past few decades there has been a Renaissance in its utilization in genomic and genetic approaches to investigating physiological, developmental, and evolutionary aspects of land plant biology. The reasons for its adoption are similar to those of other genetic models, e.g. simple cultivation, ready access via its worldwide distribution, ease of crossing, facile genetics, and more recently, eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 273 publications
0
25
0
Order By: Relevance
“…The functional conservation of divergent executioner domains in N. benthamiana prompted us to examine whether MAEPL-CC OG3 activates immune responses in non-flowering plants. To address this, we used the model experimental liverwort M. polymorpha , a bryophyte species that diverged from N. benthamiana over 450 million years ago 38 . Using an estradiol-based (XVE) conditional expression system 39 , we interrogated the function of the MpCNL1 (Mp3g01950) MAEPL-CC OG3 domain in the wild-type TAK1 accession.…”
Section: Resultsmentioning
confidence: 99%
“…The functional conservation of divergent executioner domains in N. benthamiana prompted us to examine whether MAEPL-CC OG3 activates immune responses in non-flowering plants. To address this, we used the model experimental liverwort M. polymorpha , a bryophyte species that diverged from N. benthamiana over 450 million years ago 38 . Using an estradiol-based (XVE) conditional expression system 39 , we interrogated the function of the MpCNL1 (Mp3g01950) MAEPL-CC OG3 domain in the wild-type TAK1 accession.…”
Section: Resultsmentioning
confidence: 99%
“…The conservation of genome size and number of chromosomes amongst hornworts (generally 6; (Villarreal and Renner, 2013) and liverworts (always 9 ; (Bowman et al, 2022) is also in support of a general conservation of architecture of genomes across bryophytes with deviation of this state possible in mosses with much larger genomes.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we demonstrated that a comparable global and even distribution of the chromatin modifications shapes the global architecture of the genome of the hornwort, A. agrestis . The conservation of genome size and number of chromosomes amongst hornworts (generally 6; (Villarreal and Renner, 2013) and liverworts (always 9; (Bowman et al, 2022) is also in support of a general conservation of architecture of genomes across bryophytes with deviation of this state possible in mosses with much larger genomes.…”
Section: Discussionmentioning
confidence: 57%
“…The liverwort Marchantia polymorpha is considered a model system of nonseed plants because of its molecular and genetic resourses and because it is one of the first land plants (Delwiche et al, 2017;Bowman et al, 2022). Besides this interesting evolutionary position, M. polymorpha has a sequenced genome with an estimated c. 20 000 genes, it has a dominant haploid gametophytic lifestyle, and is easily cultured and propagated (asexually via gemmae and sexually via spores) in the lab (Bowman et al, 2017;Kohchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%